2022
DOI: 10.3390/ijms24010556
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ion Permeation of the KcsA Channel by Applied Midinfrared Field

Abstract: Ion transport molecules are involved in many physiological and pathological processes and are considered potential targets for cancer treatment. In the large family of ion transport molecules, potassium (K) ion channels, as surface-expressed proteins, show the highest variability and most frequent expression changes in many tumor types. The key to exploring the permeation of K+ through potassium channels lies in the conserved sequence TVGYG, which is common in the selectivity filter (SF) region of all potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In 2018, Kopec et al 87 performed Brownian dynamics simulations on KcsA and found that the energy distribution caused by Coulomb interactions in the "hard knock-on" model may be the reason for its higher ion permeability than the water-mediated "soft knock-on" model. 175 Furthermore, Oiki et al 176,177 revealed that varying solution concentrations affect the distribution of potassium ions in the SF region, leading to the identification of a new conduction mechanism known as the "sparse ion array" model. The de Groot group applied MD simulation and the Markov state model (MSM) to study the influence of different factors such as potassium ions concentration, temperature, and membrane potential on the ion conduction and permeation process in MthK and observed that the infiltration mode is still a "hard knock-on" model, and no water infiltration phenomenon was observed.…”
Section: Ion Conduction and Permeation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Kopec et al 87 performed Brownian dynamics simulations on KcsA and found that the energy distribution caused by Coulomb interactions in the "hard knock-on" model may be the reason for its higher ion permeability than the water-mediated "soft knock-on" model. 175 Furthermore, Oiki et al 176,177 revealed that varying solution concentrations affect the distribution of potassium ions in the SF region, leading to the identification of a new conduction mechanism known as the "sparse ion array" model. The de Groot group applied MD simulation and the Markov state model (MSM) to study the influence of different factors such as potassium ions concentration, temperature, and membrane potential on the ion conduction and permeation process in MthK and observed that the infiltration mode is still a "hard knock-on" model, and no water infiltration phenomenon was observed.…”
Section: Ion Conduction and Permeation Mechanismmentioning
confidence: 99%
“…This result verified the “hard knock‐on” model from the computational perspective. In 2018, Kopec et al 87 performed Brownian dynamics simulations on KcsA and found that the energy distribution caused by Coulomb interactions in the “hard knock‐on” model may be the reason for its higher ion permeability than the water‐mediated “soft knock‐on” model 175 . Furthermore, Oiki et al 176,177 revealed that varying solution concentrations affect the distribution of potassium ions in the SF region, leading to the identification of a new conduction mechanism known as the “sparse ion array” model.…”
Section: Function and Molecular Mechanism Studies Of K+ Channelsmentioning
confidence: 99%
“…They argued that the mechanism that occurs during the transport of K + is related to its concentration in the system, that the higher the concentration of K + the fewer water molecules there will be at the SF site, and that there should not be a single permeation mechanism [ 26 ]. In our previous work, we found that the direct Coulomb knock-on mechanism is the most efficient for the transport rate of K + and is the dominant permeation mechanism throughout the simulation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of calcium channels by 42.55 THz EM waves can significantly enhance the selectivity and conductivity of calcium ions, thereby correcting the calcium current reduction caused by calcium channel defects [ 33 ]. In our previous work, a THz field with a frequency of 51.87 THz incident along the direction of the ion flow can significantly the K + flow in the KcsA channel, thus inducing rapid apoptosis of tumor cells with potassium overload [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation